Implementation Of A Problem-Based Learning Strategy (Spbm) To Improve Problem-Solving Abilities Of Spatial Geometry In Class XII Students Of SMA Negeri 1 Siborongborong Hold Study 2019/2020 - Siregar, Marsarana (Al'Adzkiya Journal, 2021)
The purpose of this study is: To find out whether the application of Problem Based Learning Strategy (SPBM) can improve students' mathematical problem solving abilities on the subject of Spatial Geometry in Class XII Students of SMA Negeri 1 Siborongborong in the 2019/2020 Academic Year. The subjects in this study were Class XII students of SMA Negeri 1 Siborongborong for the academic year 2019/2020 with a total of 34 people. The object in this study is the students' mathematical problem solving ability during the implementation of learning through Problem Based Learning Strategies (SPBM) on the subject matter of Spatial Geometry in Class XII Students of SMA Negeri 1 Siborongborong for the 2019/2020 academic year. The instrument used is a test consisting of 5 questions. The test results after action I, classically obtained the level of problem solving ability of 82.40% with an average of 74.24 this shows that students' mathematical problem solving abilities have increased to the medium category. The average teacher activity in managing learning in the first cycle at the first meeting was 3.50 in the